2021
DOI: 10.1111/ajd.13671
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of sirolimus in dermatological conditions

Abstract: Sirolimus is a mammalian target of rapamycin inhibitor (mTORI) with anti-proliferative, antiangiogenic and immunosuppressive properties. While approved in Australia as an anti-rejection medication for renal transplant patients, there is mounting evidence regarding the utility of oral and topical sirolimus in treating a plethora of dermatological conditions or conditions with cutaneous manifestations. Our aim was to present an overview of the evidence for current usage and breadth of the application of sirolimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…The potential uses of topical sirolimus include treatment of genodermatoses such as tuberous sclerosis, pachyonychia congenita, epidermolysis bullosa simplex, and neurofibromatosis; inflammatory conditions such as lichen planus; and vascular conditions such as Kaposi sarcoma, Klippel-Trenaunay syndrome, port wine stains, and tufted angiomas. 8…”
Section: Discussionmentioning
confidence: 99%
“…The potential uses of topical sirolimus include treatment of genodermatoses such as tuberous sclerosis, pachyonychia congenita, epidermolysis bullosa simplex, and neurofibromatosis; inflammatory conditions such as lichen planus; and vascular conditions such as Kaposi sarcoma, Klippel-Trenaunay syndrome, port wine stains, and tufted angiomas. 8…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin (Sirolimus) is an inhibitor of mammalian target of rapamycin (mTOR), with anti-proliferative, antiangiogenic, and immunosuppressive properties [172]. Rapamycin is used to prevent organ transplant rejection and treat lymphangioleiomyomatosis, a rare lung disease [173,174].…”
Section: Rapamycinmentioning
confidence: 99%
“…Initially described as an antifungal agent (Vezina et al, 1975), it was later found to possess potent immunosuppressive properties (Abraham & Wiederrecht, 1996). Subsequent research has uncovered its diverse therapeutic potential, ranging from its use in preventing organ transplant rejection and coronary stent restenosis, to the treatment of lymphangioleiomyomatosis, skin disorders, cancer and age-related diseases (Abraham & Wiederrecht, 1996; Ali et al, 2022; McCormack et al, 2011; Morice et al, 2002; Selvarani et al, 2021; Swarbrick et al, 2021). The various biological and therapeutic effects of rapamycin are primarily attributed to inhibition of mechanistic target of rapamycin kinase (mTOR).…”
Section: Introductionmentioning
confidence: 99%